2004
DOI: 10.7202/007769ar
|View full text |Cite
|
Sign up to set email alerts
|

L’expérience maternelle et la consommation de substances psychoactives1

Abstract: L‘article présente certains résultats d’une recherche empirique, menée selon une approche à la fois quantitative et qualitative, auprès de femmes ayant récemment accouché et consommatrices de substances psychoactives. L’objectif de cette recherche était d’améliorer les connaissances sur l’expérience de ces femmes pour soutenir le développement de services pouvant répondre adéquatement à leurs besoins. Les données indiquent, d’une part, que ces femmes ont vécu dans l’enfance et pendant leur adolescence des expé… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
3
0
2
Order By: Relevance
“…Mothers of our sample see motherhood not only as an incentive to change (De Koninck et al, 2003; Ferraro & Moe, 2003; Haight et al, 2009) but also, and mainly, as an opportunity to heal their wounded maternal identities and fulfill their unmet emotional needs. In Coyer (2000), addicted women reported that they had trouble building a maternal identity because of the abuse and neglect they had experienced.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mothers of our sample see motherhood not only as an incentive to change (De Koninck et al, 2003; Ferraro & Moe, 2003; Haight et al, 2009) but also, and mainly, as an opportunity to heal their wounded maternal identities and fulfill their unmet emotional needs. In Coyer (2000), addicted women reported that they had trouble building a maternal identity because of the abuse and neglect they had experienced.…”
Section: Resultsmentioning
confidence: 99%
“…Studies on the motherhood experience of substance-using women usually fall into two distinct categories. The first shows some evidence that the responsibilities of motherhood and social expectations toward mothers can motivate such women to curtail their use of drugs and make other positive lifestyle changes (Boyd, 1999; De Koninck, Guyon, & Morissette, 2003; Dunlap, Stürzenhofecker, & Johnson, 2006; Ferraro & Moe, 2003; Haight, Carter-Black, & Sheridan, 2009; Hardesty & Black, 1999; Taylor, 1998). Other studies show that for many women, drug use continues to influence their experience of motherhood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Malgré que leur scolarité soit peu avancée, un constat relevé également par d'autres études montre [5,[27][28][29] : 47,1 % des femmes consommatrices de substances psychoactives de notre échantillon sont actives professionnellement. Cela peut paraître étonnant, mais s'explique tout simplement par le fait qu'elles sont contraintes de travailler pour subvenir à leurs besoins de consommation, en absence d'aide familiale et sociale.…”
Section: Discussionunclassified
“…Une autre caractéristique des femmes consommatrices de substances psycho-actives est le fait qu'elles seraient plus susceptibles que les autres femmes, et même que les consommateurs masculins, d'avoir subi des abus sexuels, physiques ou émotionnels lorsqu'elles étaient enfants [7,25,29,31,32]. D'après les écrits de Hutchins, 28 % à 44 % des femmes consommatrices de substances psycho-actives ont été victimes d'inceste, taux qui se compare à 5 % dans la population générale [30].…”
Section: Discussionunclassified